The Influence of Human Resource Competency on the Effectiveness of Employee Work at the Regional Financial and Asset Management Agency of West Sumbawa Regency - Uslah, Meilsya Baraka; Lukitasari, Diah; Dianti, Ira (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The author's aim in conducting this research is to find out how human resource competence greatly influences employee performance. With increasing demands for efficiency and effectiveness in managing regional finances and assets, this research becomes relevant for improving organizational performance. This research used quantitative methods with a sample size of 75 people. The research method used is simple linear regression. The result is a significant value of 0.601, meaning 0.601 is greater than 0.05. Thus, in particular, human resource competency does not have a positive influence on employee work effectiveness. This means that human resource competency has been proven not to influence the effectiveness of the work of the West Sumbawa Regency Regional Financial and Asset Management Agency in its work.